Knowledge Transfer Services - Albert Simard (Revue de Géographie Alpine)
This paper describes a model intended to increase understanding of how content is transferred from its source to its use. A Natural Resources Canada task group explored the nature of knowledge transfer with a services paradigm to discover and understand underlying patterns and processes. Knowledge Services are programs that produce and pro-vide content-based organizational outputs with embedded value that are intended to be used internally or transferred to meet external user wants or needs. Model design criteria include independence from content, an organizational focus, scalability, two drivers, and two levels of resolution. The model is based on a value chain in which value is embedded, advanced, or extracted. A knowledge services system comprises nine stages: generate, transform, manage, use internally, transfer, add value, use professionally, use personally, and evaluate. Knowledge services are delivered through a delivery spectrum ranging from rich to reach. Each region of the delivery spectrum has a set of attributes that influence how services should be delivered.